Utilization of Technology in Pediatric Critical Care: A Systematic Review of Monitoring and Support Systems - Alkhaiat, Mohamed Magdy; Alhelali, Ibrahim; AL-Benhassan, Ibrahim; Baoqbah, Abdullah; Alhazmi, Ahmed; Almusdi, Mohammed Mahmoud (Journal of Ecohumanism, 2025)
Background: Pediatric critical care systems have benefited from technological developments that deliver artificial intelligence (AI) applications along with telemedicine features and Internet of Things (IoT)-based observation frameworks. Advanced medical technology enhancements produced better patient results and faster detection of vital health changes and increased operation effectiveness. The high implementation costs along with system compatibility issues and ethical constraints remain as barriers to widespread adoption. Aim: This systematic review explores how technology for advanced monitoring and support systems has affected patient care results and workflow effectiveness in pediatric critical care settings. Method: Researchers carried out the review according to PRISMA instructions while performing systematic searches across PubMed with Scopus Web of Science and CINAHL databases. Title/abstract screening alongside duplicate removal and full-text review reduced 1,568 studies to ten high-quality ones. Data extraction to evaluate study design characteristics together with technology type implementation outcomes alongside challenges encountered. Results: Three main themes emerged: supportive leadership, organizational support and crisis management. All three types of leadership examined (relational, servant, and transformational) were positively linked to resilience and well-being. Significant mitigating factors included organizational support through resource allocation, training, and mental health initiatives. It was found that adaptive leadership and effective communication were important for success during crises, particularly to retain staff morale and staff cohesion. All ten studies fulfilled the review’s role with regard to the multifaceted role of nurse leaders promoting resilience. Conclusion: Pediatric critical care technologies deliver transformative abilities which boost both patient health outcomes and operational performance. The adoption of new technologies requires strategic solutions to overcome cost expenses and training needs and to achieve effective system integration. Subsequent research needs to emphasize standardizing procedures and ethical principles and finding cost-efficient approaches to maximize technological advances in this field.